(untitled) (Journal of Enam Medical College, 2015)
The existence of confusing drug names is one of the most common causes of medication errors. There are many types of medication errors: wrong drug, wrong dose, wrong route of administration, wrong patient etc. Misreading medication names that look similar is a common mistake. These look-alike medication names may also sound alike and can lead to errors associated with verbal prescriptions. Similar sounding drugs may produce confusion and may lead to unintended interchange of drugs causing harm to patients or even patient death. The main aim of the study was to evaluate medication errors related to look alikesound alike drug names and to find out the strategies to prevent these medication errors. J Enam Med Col 2015; 5(2): 110-117